Mueller-matrix reconstruction of parameters of phase and amplitude anisotropy in diagnostics of endometriosis and infertility - Ushenko, A.G.; Dominikov, M.M.; Lakusta, I.I.; Koval, G.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
A new azimuthally stable polarimetric method for processing microscopic images of optically anisotropic structures for different biological layers of histological sections has been proposed. A new model that enables to determine phase anisotropy of biological tissues by using superposition of Mueller matrices of linear birefringence and optical activity has been proposed. The matrix element M₄₄ has been chosen as the main information parameter, which value is independent of rotation angle of both sample and probing beam polarization plane.